Power Doppler sonography in the assessment of neovascularization following surgical fracture repair in sheep: case report - Baccarelli, Danielle Cristinne; Paretsis, Nicole Fidalgo; Lhamas, Cínthia Lima; Corrêa, Rodrigo Romero; Spagnolo, Júlio David; Benesi, Fernando José; Manchini, Giuliana; Zoppa, André Luis do Valle de (Brazilian Journal of Veterinary Research and Animal Science, 2017)
Sonography is a safe and non-invasive imaging modality, with the added benefit of providing dynamic images. Power Doppler sonography allows blood vessel identification regardless of flow intensity or direction. A one-year-old Ile de France ewe was admitted to the FMVZ-USP Veterinary Hospital with a complete tibial fracture. The animal was submitted to general inhalation anesthesia and fracture repair using a 3.5 mm locking compression plate. Power Doppler sonography was used to assess neovascularization over the course of the bone healing process. Formation of new vessels was noted between postoperative days 14 and 21; new vessels regressed progressively on subsequent assessments (postoperative days 28 and 35). Power Doppler sonography enabled early detection of newly formed blood vessels at the fracture site. The non-invasive nature of this imaging modality prevented patient stress and provided useful information on the progression of bone healing. Early neovascularization was thought to reflect successful postoperative healing of the tibial fracture described.